2021
DOI: 10.3389/fpsyt.2021.690295
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Its Association With Quality of Life in Organ Transplant Recipients During COVID-19 Pandemic

Abstract: Objectives: The coronavirus disease 2019 (COVID-19) pandemic may have an impact on the psychological distress of organ transplant recipients. We aimed to assess the status of psychological distress and its association with quality of life (QoL) in organ transplant recipients during the COVID-19 pandemic.Materials and Methods: A cross-sectional survey was carried out with 305 organ transplant recipients during March 30 and April 2, 2020, in Wuhan. Psychological distress comprised depression, anxiety, insomnia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
2
4
0
1
Order By: Relevance
“…Psychological distress has a significant direct effect on the QOL of older adult individuals. This conclusion is consistent with previous research ( 50 ). Psychological distress should be taken seriously as a risk factor affecting the QOL of older adult individuals.…”
Section: Discussionsupporting
confidence: 94%
“…Psychological distress has a significant direct effect on the QOL of older adult individuals. This conclusion is consistent with previous research ( 50 ). Psychological distress should be taken seriously as a risk factor affecting the QOL of older adult individuals.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, we found high rates of stress and anxiety in this vulnerable patient group. This is in line with previous studies that have also described extensive psychological influences of the COVID-19 pandemic and lockdown measures in both patients with type 1 diabetes, and (solid) organ transplant recipients [4,5,10,[36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 91%
“… 7 Another study conducted with organ recipients in China between March – April 2020 found that 30.5% of participants struggled with PTSD and 13.4% with depression. 8 This study found that transplant recipients with depression scored significantly lower on all areas of a Quality of Life Questionnaire, with reports of worsened physical health, pain, vitality, and emotional state. To truly understand patients’ lived experience during a global pandemic, we created the COVID-19 Kidney and Transplant Listening and Resource Center (KTLRC), a telephone hotline to learn, in real-time, about the specific challenges and stressors that dialysis and transplant patients were facing and to disseminate transplant-related education about COVID-19, including mental health resources.…”
Section: Introductionmentioning
confidence: 65%